Kecendrungan pilihan minat karir melanjutkan perkuliahan dilihat dari teory reo personality - Vivi Sumanti; Mega Iswari (SCHOULID: Indonesian Journal of School Counseling, 2023)
This study aims to study the trend of career interest in continuing lectures based on the theory of reo personality. This research is a literature article with a literature review method, which is targeted at several sources of articles, books from various selected journals that are adapted to this article. Furthermore, this research is also to find out the tendency of a person's choice of career interests to continue college can be seen based on the theory of reo. Based on this research, it can be concluded that the tendency of students' career choices tends to be environmental and family factors, which are dominated by parents, because habits that are often carried out on something from childhood can be developed into a career in the future. Furthermore, the results of this study can be used as a basis for providing guidance and counseling services that are formulated in service programs by counselors in schools and for further researchers to conduct descriptive qualitative research on the reasons and factors in career choice as well as correlation research on career selection factors with abilities. career choice